Evaluasi Desain Toilet Umum di Gedung Laboratorium Teknik 2 ITERA dengan pendekatan Ergonomi - Yurim Hatamaiya Setyorini (Jurusan Teknologi Produksi dan Industri, Institut Teknologi Sumatera, 2022)
As a service room, the function of the toilet in the campus building is very important. A good toilet design will create a healthy space and make the toilet work well. Toilets as rooms with complex utilities are often not designed according to standards. Utility standards in the form of lighting, ventilation, plumbing in some designs are often ignored. This study will discuss the design evaluation on the working drawings and the design of the toilet building on the 2nd floor of the Engineering Laboratory 2, Sumatra Institute of Technology. The research was conducted using a qualitative method by means of surveys, and primary and secondary documentation studies. The results of the study were in the form of evaluation of the design and design of the toilet building in Engineering laboratorium 2 building that will produce recommendations for the right toilet design in terms of utility.